What is the Value Added by High-School Infrastructure and Teacher Qualities on Student Grades? - Soares, Joseph A; Bandyk, Stephanie A. (Advances in Social Sciences Research Journal, 2016)
The assumption that high-school infrastructure and teacher quality have positive impacts on academic attainments was challenged when Massey and Fischer disclosed a double paradox. First, infrastructure quality has a negative effect on high school GPA (Massey, Charles, Lundy, and Fischer, 2003) and a positive effect on college GPA (Fischer, 2007). And second, teacher quality does not impact GPA, but teachers’ disciplinary practices do. How can the same infrastructure have opposite effects on grades when one looks at high school versus college? And why does teacher quality not matter, but disciplinary behavior does matter, to academic performance? Using data from the National Longitudinal Survey of Freshmen, this study analyzes particular measures of school infrastructure to ascertain their effects on grades in high school and college. Our results suggest that the aspect of infrastructure quality that positively affected freshman GPA was overall school quality, while the aspects that negatively affected high school GPA were library quality and school’s reputation in the community. Further, teacher quality was not found to be a positive and significant predictor of GPA at either the high school or university level. However, teachers’ disciplinary practices, when perceived as either “fair” or “strict” by students, did matter. When discipline was perceived as “fair”, there was a positive correlation with high school GPA, and conversely when it was perceived as being “strict” there was a negative impact on high school GPA. This research provides new evidence regarding how particular aspects of infrastructure and teacher qualities precisely affect GPA at both high school and college levels. Studies that do not work with these measures will misestimate the impact of school resources on outcomes.